2022
DOI: 10.3390/plants11030333
|View full text |Cite
|
Sign up to set email alerts
|

The Phenolic Content, Antioxidative Properties and Extractable Substances in Silver Fir (Abies alba Mill.) Branches Decrease with Distance from the Trunk

Abstract: Silver fir (Abies alba Mill.) is one of the most common and valuable conifer tree species in Central Europe, with well-established usage in the construction and furniture industries, as well as the food, health products, pharmaceuticals and cosmetics industries. Silver fir branch extract, a mixture of antioxidative phenols, is produced industrially as a food supplement with a wide range of therapeutic properties. This study investigates optimization of the production of silver fir branch extract by researching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Bhardwaj et al (2021) reported several constituents present in conifers, amongst other phytochemicals: quercetin, rutin, (+)-catechin, caffeic acid, cinnamic acid, syringic acid, chlorogenic acid, and t-resveratrol, which were identified in SP, PI, DO, and LA [16]. Also, the antioxidant activity and the total polyphenolic content were confirmed for all the extracts analyzed in this study [16,25].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Bhardwaj et al (2021) reported several constituents present in conifers, amongst other phytochemicals: quercetin, rutin, (+)-catechin, caffeic acid, cinnamic acid, syringic acid, chlorogenic acid, and t-resveratrol, which were identified in SP, PI, DO, and LA [16]. Also, the antioxidant activity and the total polyphenolic content were confirmed for all the extracts analyzed in this study [16,25].…”
Section: Discussionsupporting
confidence: 69%
“…are commonly found in European forests. Their extracts can be considered a source of phytochemicals, and they can be used for the preservation of human health because of their antioxidant and antimicrobial properties [ 16 , 22 , 23 , 24 , 25 ]. Several phenolic compounds can be quantified in extracts from these conifers, such as gallic acid, caffeic acid, syringic acid, p-coumaric acid, ferulic acid, chlorogenic acid, vanillic acid, t-cinnamic acid, catechin, rutin, quercetin, apigenin, kaempherol, luteolin, etc., and they can provide antimicrobial activity against several bacteria and fungi like Pseudomonas aeruginosa , Acinetobacter baumannii , Klebsiella pneumoniae , Enterococcus faecium , Staphylococcus aureus , Candida sp., Aspergilius sp., etc.…”
Section: Introductionmentioning
confidence: 99%
“…is a popular and valuable medicinal plant that has been utilized in the food, pharmaceuticals, and cosmetics industries for its many various health-promoting properties. It is abundant in phenolic acids, lignans, and flavonoids [ 110 , 111 ]. Belinal, a standardized polyphenolic extract of silver fir ( Abies alba L.) branches, exhibited a significant chondrogenesis effect in bone-derived mesenchymal stem/stromal cells derived from patients with hip OA [ 106 ].…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 99%
“…For branches, it was reported that optimal extraction might be obtained at a temperature of 100 • C, using a sample-to-water ratio of 1:10 and a relatively long extraction time (90 min). The extractable constituents of branches dropped by about 40% as the portion sampled was farther away from the trunk [13].…”
Section: Parts Used and Extraction Methodsmentioning
confidence: 99%
“…Publications in the English, French, or German languages were retained for analysis and synthesis in this review. In the 19th century, its use for food purposes was first proposed in the form of s fir beer [13]. Recently, an extract obtained from its needles was proposed to be use whole wheat bread enrichment in a proportion of up to 35% (the threshold of taste ception), its addition increasing the antioxidant properties of the bread and the tec logical qualities of the dough and bread [14].…”
Section: Introductionmentioning
confidence: 99%